2017
DOI: 10.1245/s10434-017-5776-8
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Impact of Unplanned Excisions in a Cohort of 728 Soft Tissue Sarcoma Patients: A Multicentre Study

Abstract: BackgroundUnplanned excisions (UE) of soft tissue sarcomas (STS) carry a high risk for local recurrence (LR) due to marginal/intralesional resections. However, there are reports about improved prognosis for UE patients who have re-resection compared with patients who undergo planned surgery. The present multicentre study was designed to define characteristics of UE patients and to investigate the impact of UE on subsequent therapy and patient outcomes.MethodsA total of 728 STS patients (376 males, 352 females;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
65
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 72 publications
(82 citation statements)
references
References 23 publications
(32 reference statements)
2
65
0
2
Order By: Relevance
“…Soft tissue sarcomas of the extremity and trunk (STS) are rare tumours with an estimated incidence of 2.4 cases per 100 000 persons per year 1 . About 15% of STS‐patients develop local recurrences and 30% distant metastases at 5 years, most commonly to the lungs 2‐5 . Other metastatic sites are described (bone and lymph nodes), however abdominal metastases (AM) from STS, are very uncommon 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…Soft tissue sarcomas of the extremity and trunk (STS) are rare tumours with an estimated incidence of 2.4 cases per 100 000 persons per year 1 . About 15% of STS‐patients develop local recurrences and 30% distant metastases at 5 years, most commonly to the lungs 2‐5 . Other metastatic sites are described (bone and lymph nodes), however abdominal metastases (AM) from STS, are very uncommon 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…However, after the re‐excision of an STS with wide or negative resection margins, some studies have found local recurrence, metastasis, and survival rates similar to those after an initial primary surgery . Several publications have even stated that patients who undergo re‐excision surgery have superior oncologic outcomes in comparison with those who undergo primary surgery . These previous studies included all patients with unplanned excisions of extremity STS, including those with small and superficial tumors, whose outcomes are expected to be superior, and those with large and deep tumors, which would be associated with worse prognoses.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of unplanned, nononcologic excisions on oncologic outcomes for patients with truncal or extremity STS is disputed. Previous studies demonstrate conflicting results as some groups report worse outcomes with patients who undergo UE primarily, while others report similar or even improved outcomes compared with patients who undergo PE . This incongruence in results is explained by the difficulty in comparing patients who undergo UE to patients who undergo PE given the more favorable tumor characteristics (smaller size and more superficial location) in patients who undergo UE primarily.…”
Section: Discussionmentioning
confidence: 99%
“…The cornerstone of curative treatment for patients with localized soft tissue sarcoma (STS) of the trunk or extremity is oncologic surgical resection with or without radiation . Due to the rarity of STS compared to the prevalence of benign soft tissue masses, up to 50% of patients with STS will undergo a nononcologic, unplanned excision (UE) for a mass initially presumed to be benign . Patients who undergo unplanned, nononcologic resections are commonly referred to tertiary referral centers, and due to the high probability of residual tumor left in the surgical bed after UE, the current standard of care recommends re‐excision with or without radiation of the tumor bed in an effort to achieve appropriate oncologic margins and local control …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation